Light‐Gated Molecular Brakes Based on Pentiptycene‐Incorporated Azobenzenes. Issue 4 (5th February 2015) - Tan, Wei Shyang; Chuang, Po‐Ya; Chen, Chia‐Huei; Prabhakar, Chetti; Huang, Shing‐Jong; Huang, Shou‐Ling; Liu, Yi‐Hung; Lin, Ying‐Chih; Peng, Shie‐Ming; Yang, Jye‐Shane
Abstract: Three azobenzene derivatives (2 R, 2 OR, and2 NR ) that differed in their terminal substituent (alkyl, alkyloxy, and dialkylamino, respectively) have been synthesized and investigated as molecular brakes, in which the rigid H‐shaped pentiptycene group functioned as a rotor and the dinitrophenyl group as a "brake pad". The E and Z isomers of these compounds corresponded to the "brake‐off" and "brake‐on" states, respectively. The rotation rate of the rotor was evaluated by VT NMR spectroscopy for the brake‐on state and by DFT calculations for the brake‐off state. The difference between the rotation rates for the rotor in the two states was as large as eight orders of magnitude at ambient temperature. Photochemical switching of the azobenzene moieties afforded efficiencies of 55–67 %. A combination of photochemical E → Z and thermal Z → E isomerization promoted the switching efficiency up to 78 %. The terminal substituent affected both the photochemical and thermal switching efficiencies. Solvent polarity also played an important role in the lifetimes of the Z isomers. These azobenzene systems displayed similar braking powers but superior switching efficiencies to the stilbene analogue (1O R ; ca. 60 % vs 20 %). Abstract : Braking pad : Three azobenzene derivatives that differed in their terminal substituent were investigated as molecular brakes, in which the rigid H‐shaped pentiptycene group functioned as a rotor and the dinitrophenyl group as a brake pad. They are superior to the stilbene counterparts in the on‐off switching efficiency.